A new species of Brachycephalus (Anura, Brachycephalidae) from the coast of Santa Catarina State, southern Atlantic Forest, Brazil - De Carli Monteiro, Juliane Petry [UNESP]; Condez, Thais Helena [UNESP]; De Anchietta Garcia, Paulo Christiano; Comitti, Estevao Jasper; Amaral, Ivan Borel; Baptista Haddad, Celio Fernando [UNESP] (Magnolia Press, 2018)
We describe a new species of Brachycephalus from municipality of Sao Francisco do Sul and municipality of Itapoa, in the state of Santa Catarina, Brazil, southern Atlantic Forest. The new species is known from six localities from near sea level up to 250 meters and represents the first record of a pumpkin-toadlet occurring in the lowlands. Morphological traits and phylogenetic analysis of a fragment the 16S mtDNA gene place the new species in the Brachycephalus pernix group. The new species is supported by external morphology, osteology, advertisement call, and mtDNA divergence. It is characterized, among other traits by a dorsal body color dark green with a dark brown vertebral stripe, and an orange background; snout-vent length of 9.2-10.8 mm in males and 11.1-12.4 mm in females; and advertisement call short (0.02-0.03 seconds), composed of one high-frequency note (dominant frequency 6.6-7.3 kHz). We observed synchronized alternation in the emission of vocalizations among neighbor males, indicating that males of the new species are able to hear and use vocalizations to interact with each other. We provide descriptions of clutch, eggs, and juvenile and observations on parental care. The new species has not been recorded within any protected area and can be threatened by human-induced habitat loss and modification.
Keywords: Brachycephaloidea; elevational range; morphology; taxonomy